Correlation of Mature Cystic Teratomas With CA19-9 - Dr. Amneh Khairullah Mughir1; Dr. Nadia Mudher Al-Hilli (Academic Journal of Clinicians, 2022)
Background: Mature cystic teratomas are the most common germ cell tumor account 10-20% of all ovarian tumors. Several tumor markers have been linked to their presence & development of complications. Objective: To evaluate the relation between mature cystic teratomas with tumor marker CA19.9.Patients and Methods: A case-control study conducted in Babylon Teaching Hospital for gynecology & Pediatrics & private clinic during the period February-December 2018 included, 50 women with ovarian dermoid cyst and 50 healthy women as controls, full history & thorough clinical examination were done and further investigation performed accordingly. CA19.9 level was investigated in blood samples. Surgery in form of laparoscopy or laparotomy was done for dermoid cyst patients & specimens sent for histopathology to confirm diagnosis. Results: CA19.9 was significantly higher in patients with dermoid cyst compared to that in control, 46.5. ± 23.84 vs. 11.22 ± 3..8 respectively. (p < 0.001).The receiver operating characteristic (ROC) curve analysis revealed that CA19.9 produced a sensitivity of .2%, specificity of 96%, accuracy of 84%, positive predictive value of 95% and negative predictive value of ..%. According to these values of validity, CA19-9 was good enough to predict ovarian dermoid cyst. There was positive correlation with diameter of the dermoid cyst. Conclusion: CA19.9 was significantly correlated with and good predictor of dermoid cyst. A strong correlation exists between CA19.9 level and the diameter of the tumor.